Stability of functional equations and properties of groups - Forti, Gian Luigi (Annales Mathematicae Silesianae, 2019)
Investigating Hyers–Ulam stability of the additive Cauchy equation with domain in a group G, in order to obtain an additive function approximating the given almost additive one we need some properties of G, starting from commutativity to others more sophisticated. The aim of this survey is to present these properties and compare, as far as possible, the classes of groups involved.